2015
DOI: 10.1096/fj.15-270611
|View full text |Cite
|
Sign up to set email alerts
|

Cleaving for growth: threonine aspartase 1—a protease relevant for development and disease

Abstract: From the beginning of life, proteases are

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 72 publications
0
10
0
Order By: Relevance
“…Proteolysis is an essential process in biology with roles as diverse as protein turnover, signaling regulation, and ECM modification; moreover, it is also the basis of various pathologies including cancer. One of the highly conserved proteases Threonine Aspartase 1 (Taspase 1) is overexpressed in multiple cancer conditions (Stauber et al, 2016). As current knowledge regarding the substrate specificity and regulatory mechanism of Taspase 1 is limited, CVM cell migration can potentially serve as a valuable model system to study this gene.…”
Section: Resultsmentioning
confidence: 99%
“…Proteolysis is an essential process in biology with roles as diverse as protein turnover, signaling regulation, and ECM modification; moreover, it is also the basis of various pathologies including cancer. One of the highly conserved proteases Threonine Aspartase 1 (Taspase 1) is overexpressed in multiple cancer conditions (Stauber et al, 2016). As current knowledge regarding the substrate specificity and regulatory mechanism of Taspase 1 is limited, CVM cell migration can potentially serve as a valuable model system to study this gene.…”
Section: Resultsmentioning
confidence: 99%
“…Taspase is a conserved threonine-aspartic acid protease that cleaves mammalian and Drosophila MLL1/trithorax, as well as other nuclear proteins ( e.g. , TFIIA) associated with chromatin and transcription; mutations in human Taspase1 have been associated with certain forms of cancer, particularly those of the head and neck ( Hsieh et al 2003a ; Hsieh et al 2003b ; Khan et al 2005 ; Takeda et al 2006 ; Zhou et al 2006 ; Oyama et al 2013 ; Niizuma et al 2015 ; Takeda et al 2015 ; Stauber et al 2016 ; Gribko et al 2017 ). The four independent mutations are placed on the tasp-1 genomic locus as shown in Figure 5A .…”
Section: Resultsmentioning
confidence: 99%
“…Focusing on disease-relevant signalling-pathways in head and neck cancer, the Taspase1-TFIIA-CDKN2A axis is an interesting and potentially druggable target for HNSCC. In the past it could be demonstrated that Taspase1 uses different strategies to regulate biological processes like proliferation, cell cycle, differentiation and apoptosis 11 , 19 . Interestingly, our data support the hypothesis that Taspase1 fine-tunes the transcriptional activity of TFIIA via its subcellular localization and proteolytic cleavage.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the exclusively cis -active type 2 asparaginases, only Taspase1 is able to cleave distinct substrates in trans by hydrolyzing its target proteins at conserved (Q 3 [FILV] 2 D 1 ↓G 1′ x 2′ D 3′ D 4′ ) sites 14 , 15 . During mammalian development, Taspase1 plays an important role in the regulation of correct segmental identities, head morphogenesis and spermatogenesis 16 19 . However, the molecular mechanisms how Taspase1 may affect substrate functions through site-specific proteolysis still remain to be determined.…”
Section: Introductionmentioning
confidence: 99%